IMPACT OF WOMEN COMPOSURE IN HOSPITALITY INDUSTRY - Shaikh, Mubeen Amir (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research explores the critical role of women’s composure in the hospitality industry, focusing on how their emotional stability, resilience, and interpersonal skills contribute to the industry’s operational success and customer satisfaction. Women in hospitality often encounter high-stress environments that require a balanced demeanor to handle diverse clientele, resolve conflicts, and maintain team morale. By analyzing real-world scenarios and drawing from interviews with industry professionals, this paper examines how women’s ability to remain composed under pressure enhances both guest experiences and team dynamics. The findings indicate that composure not only positively impacts immediate service quality but also strengthens long-term customer loyalty and business reputation. This study advocates for increased support and resources for women to nurture these attributes, emphasizing the need for gender-sensitive policies that recognize and harness the unique strengths women bring to the hospitality industry.